Sectoral and territorial industrial policy in the strategic documents of Russia and its regions - D. A. Gaynanov; D. M. Ataev (Вестник университета)
The article analyses the consistency of sectoral and territorial industrial policy target benchmarks reflected in federal and regional strategic documents of territorial socio-economic systems. The results of a comparison of this benchmarks showed that there is no unified approach to defining goals, quantitative and qualitative composition of target indicators of industrial development not only among strategic documents of various nature (goal-setting, forecasting, territorial, sectoral), but also within sectoral documents of industrial development in Russia and its regions. There is also no clearly defined vertical decomposition of national priorities for industrial development according to the directions and levels of strategic planning of territorial socio-economic systems.